Sex-Specific Exposure–Effect Relationship Between Physical Activity and Incident Atrial Fibrillation in the General Population: A Dose–Response Meta-Analysis of 16 Prospective Studies - Wan, Qin; Zhou, Yue; Zhu, Wengen; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Background: Since evidence regarding the relationship between physical activity (PA) and atrial fibrillation (AF) incidence is inconsistent among studies, we performed a dose–response meta-analysis to comprehensively evaluate the exposure–effect association between PA and incident AF and the potential sex difference in the general population. Methods: The PubMed and Embase databases were searched for eligible studies published up to July 2020 (PROSPERO: CRD42018091692). The non-linear or linear exposure–effect relationship between PA and AF was examined using the robust error meta-regression method. Results: A total of 16 prospective studies involving 1,449,017 individuals and 39,884 AF cases were included. We observed an inverse non-linear association between PA level and incident AF (I2 = 0%, pnon−linearity < 0.001). In the linear model, a 5 metabolic equivalent of task (MET)-h/week increase in PA was associated with a decreased risk of AF [risk ratio (RR) = 0.992, 95% confidence interval (CI): 0.988–0.996, I2 = 0%]. In the sex-stratified analysis, we observed an inverse non-linear relationship between PA level and AF risk in females (I2 = 90%, pnon−linearity < 0.0001) but not in males (I2 = 0%, pnon−linearity = 0.40). In the linear model, a 5 MET-h/week increase in PA was associated with a reduced risk of AF in females (RR = 0.982, 95% CI: 0.975–0.989, I2 = 71%) but not in males (RR = 0.998, 95% CI: 0.994–1.002, I2 = 0%), with a significant interaction observed between the two groups (pinteraction < 0.0001). Conclusion: There was an inverse non-linear relationship between PA level and incident AF in the general population. The beneficial effect of PA in reducing AF risk might be predominantly observed in females.